1994
DOI: 10.1136/ard.53.7.467
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic crystals in osteoarthritic synovial fluids.

Abstract: Objectives-To investigate the hypothesis that synovial fluid (SF) from patients with osteoarthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 10 publications
5
41
0
4
Order By: Relevance
“…Lavage of the joint clears fragments of cartilage 19 and calcium phosphate crystals. 62 Harwin 28 and other groups 16,17,56 have found that lavage and debridement are beneficial for a select group of patients presenting with acute pain, specific localized mechanical symptoms of locking or catching, minimal malalignment, and no previous history of surgery, 48 as opposed to patients with global arthritic changes. 31 Jackson and Dieterichs 33 found that lavage and debridement provide significant relief in patients with osteoarthritis if the intervention is performed during the acute stage of degeneration.…”
Section: Palliative Technique: Arthroscopic Lavage and Debridementmentioning
confidence: 99%
“…Lavage of the joint clears fragments of cartilage 19 and calcium phosphate crystals. 62 Harwin 28 and other groups 16,17,56 have found that lavage and debridement are beneficial for a select group of patients presenting with acute pain, specific localized mechanical symptoms of locking or catching, minimal malalignment, and no previous history of surgery, 48 as opposed to patients with global arthritic changes. 31 Jackson and Dieterichs 33 found that lavage and debridement provide significant relief in patients with osteoarthritis if the intervention is performed during the acute stage of degeneration.…”
Section: Palliative Technique: Arthroscopic Lavage and Debridementmentioning
confidence: 99%
“…It has been suggested recently that many OA fl uids contain clusters of BCP crystals that are too small or too few in number to be identifi ed by conventional techniques [4]. Ample data support the role of BCP crystals in cartilage degeneration.…”
Section: Clinical Aspectsmentioning
confidence: 97%
“…too small or too few in number to be identified by conven tional techniques [7]. There are as yet no studies as to whether such rare or small crystals have different clinical implications.…”
Section: The Detection and Identification Of Crystalsmentioning
confidence: 98%